Early feeding and growth pattern in infants: Using a three-variate longitudinal model derived from Gaussian copula function (Epidemiology, Biostatistics, and Public Health, 2022)
Background: The Gaussian copula model was used to generate joint distributions for continuous longitudinal variables on infant types of feeding and longitudinal measures of height, weight and head circumference Methods: The study was performed longitudinally in rural areas of southern part of Iran, on children from birth to 9 months of age. Out of 319 infants with serial anthropometric measurements from birth, and 2, 4, 6, 7 and 9 months old, 120 were included. Infants were divided into three groups (breast fed, formula fed and both milk types). A three-variate longitudinal model including Copula function was used to estimate the effect of feeding on growth pattern. All the analyses were performed using SAS version 9.4 (Proc NLmix). Results: Ninety infants (75%) were breastfed, sixteen (13.3%) were formula fed and fourteen (11.7%) had combined feeding. Copula model showed that, breast fed children had a better weight gain (β=0.627 95% CI 0.217-1.038 P = 0.003), height (β=2.603 95% CI 1.023-4.183 P = 0.001) and head circumference (β=0.8 95% CI 0.069- 1.531 P = 0.0) as compared to formula fed children. R2 for Copula model was (wt=0.52, ht=0.96, hc=0.84). Conclusions: Implication of Copula model was easy to perform. Estimation of the parameters in copula model indicated that, breast milk consumption had a positive effect on the growth of infants.